(untitled) (Revista de História da UEG (REVHIST), 2020)
School is, by its nature, a memory institution due to the way it is obliged to archive numerous documents. However, photographs, in spite of the memories they bring and the visual record they compose, are most often not the target of systematic archiving in schools. In this article, we use the circumstance of discovering old glass negatives in the bottom of a drawer in Escola Secundária de Camões as an example, and a mode to reflect on the role of photography in schools in Portugal, mobilizing the concepts of collective memory, individual and history. Keywords: School. Photography. Liceu de Camões. Archive. Memory.